Pengaruh Kualitas Pelayanan, Harga dan Citra Merek Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Pemediasi - Setyowati, Erni, Drs. Wiyadi, M.M., Ph. D, Drs. M. Farid Wajdi, M.M., Pd. D (2016)
This research aims to identify and analyze: 1) the quality of service to customers satisfaction. 2) price to customers satisfaction. 3) brand image on customers satisfaction. 4) quality of service to customers loyalty. 5) price to customers loyalty. 6) brand image to customers loyalty. 7) customers satisfaction to customers loyalty. The data of this research is the premier data which was obtained from the answers of 100 respondents with accidental sampling method. This research is using path analysis. The test result concluded that all variables instrument are valid and reliable as a data collecting tool. In thedata analysis shows that: 1) service quality has positive and significant effect on customers satisfaction. 2) price has the positive and significant impact on customers satisfaction. 3) brand image has positive and significant impact on customers satisfaction. 4) the quality of service has positive and significant effect on the customers loyalty. 5) price has positive and significant effect on customers loyalty. 6) brand image has positive and significant effect on customers loyalty. 7) customers satisfaction has positive and significant effect on the customers loyalty.